Menimbang Kritik Adnin Armas atas Hermeneutika Alquran - Saifullah, Muhammad (IAIN Surakarta, 2018)
The article is to examine Adnin Armass criticism of Quran hermeneutics. By comparing tafsir and hermeneutics of Quran, Adnin has depicted that the later was too relative for being method on Quranic interpretation. Instead, it contained the perilousÂ entity for Muslims, particularly in their identityâknowing the genealogy was from Western culture. On the contrary, tafsir was far from the relativity, native Islamic product of history,Â and subsequently being the only way to touch Quran. No more appropriate way to understand Quran, Adnin Said, except tafsir. Along the histroy of Muslims, tafsir was absolutely fruitfull. Understanding the fact, thus, the article tries to evaluate the sources used by Adnin, till refused Quranic hermeneutics and embraced tafsir as something sacred with questions how far he understood them and picked them up from. Â Â Â